The type locality of Tor mosal (Hamilton, 1822) (Teleostei: Cyprinidae) - Raghavan, Rajeev; Dahanukar, Neelesh; Britz, Ralf (Zootaxa, 2017)
Hamilton (1822) described Cyprinus mosal, now assigned to the genus Tor, from the ‘Kosi’, a tributary of the Ganges. The fact that two Gangetic tributaries with the name Kosi exist, has resulted in confusion in the Indian ichthyological literature and beyond regarding the type locality of Hamilton’s T. mosal. A critical review of Hamilton’s treatise on the fishes of the Ganges, as well as several other works by and on Hamilton, revealed that T. mosal was collected in and described from the Kosi (=Koshi), a Gangetic tributary that originates in the northern slopes of the Himalayas in the Tibet Autonomous Region and drains the southern slopes of Nepal and Bihar (India); and not from the more western Gangetic tributary by the same name flowing through Ramnagar in Uttarakhand State, India.